A Gap Analysis of Sustainability Framework in the Apparel Industry - Cemara, Gita (Dinasti Research, 2025)
The apparel industry faces growing pressure to embrace sustainability due to its substantial environmental and social footprint. This study presents a comparative gap analysis of four widely adopted sustainability frameworks: the Higg Index (FEM + FSLM), Global Recycled Standard (GRS), Zero Discharge of Hazardous Chemicals (ZDHC), and Target Corporation’s internal guidelines. Using a structured scoring matrix (0 = no coverage to 3 = full, auditable coverage), the study evaluates how each standard addresses key environmental, social, and audit-related criteria. Results show that while Higg and Target demonstrate balanced performance across both environmental and social areas, ZDHC remains narrowly focused on chemical safety, and GRS primarily on recycled content. Significant coverage gaps persist, particularly in emission tracking, labor rights enforcement, and audit harmonization. Visual and weighted analysis further confirms the fragmentation between standards. These findings highlight the urgent need for an integrated, harmonized approach to minimize redundant audits and support more efficient, credible sustainability practices.